2007
DOI: 10.1248/cpb.55.908
|View full text |Cite
|
Sign up to set email alerts
|

Lanostane-Type Triterpenoids from Diospyros discolor

Abstract: Plants in the Diospyros genus (Ebenacea) are well documented as a rich sources of naphthoquinones and triterpenes, which have been found to exhibit ichthyotoxic, 1,2) antimicrobial, [2][3][4] and antitumor activities. 4,5) Thirteen species of this genus are indigenous to Taiwan. Several species, including fruits of D. discolor WILLD., 6) leaves of D. kaki THUNB., 7) barks and stems of D. eriantha CHAMP., 8,9) stems of D. morrisiana HANCE., [10][11][12] fruits of D. ferrea, 13) and bark, root, fruits, leaves, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Its molecular formula was determined to be C 32 H 54 O from the molecular ion at m/z 455.4275 [M + H] + based on HR-ESIMS, indicating six indices of hydrogen deficiency. The IR spectrum showed absorption bands at hydroxyl (3382 cm −1 ) and terminal double bond (3043, 1371, and 890 cm −1 ) functionalities [29]. The 1 H-NMR spectrum of 17 (Table 2) indicated the presence of eight tertiary methyls [δ H 1.03, 0.97, 0.80, 0.73, 0.64 (3H each, s), and 1.04 (3H × 3, s)], one secondary methyl [δ H 0.90 (3H, d, J = 6.…”
Section: Chemical Identification Of Compounds 1-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Its molecular formula was determined to be C 32 H 54 O from the molecular ion at m/z 455.4275 [M + H] + based on HR-ESIMS, indicating six indices of hydrogen deficiency. The IR spectrum showed absorption bands at hydroxyl (3382 cm −1 ) and terminal double bond (3043, 1371, and 890 cm −1 ) functionalities [29]. The 1 H-NMR spectrum of 17 (Table 2) indicated the presence of eight tertiary methyls [δ H 1.03, 0.97, 0.80, 0.73, 0.64 (3H each, s), and 1.04 (3H × 3, s)], one secondary methyl [δ H 0.90 (3H, d, J = 6.…”
Section: Chemical Identification Of Compounds 1-19mentioning
confidence: 99%
“…This was supported by the singlet signal of three chemically equivalent methyl groups [δ H 1.04 (3H × 3, s, H-26, H-27, H-32)] observed in the 1 H-NMR spectrum of 17, which revealed the HMBC correlations with C-24 (δ C 159.2) and ROESY correlations with H-31 (δ H 4.82), elucidating the structure of the side chain as CH(CH 3 )CH 2 CH 2 C(CH 2 )C(CH 3 ) 3 (Figure 4). The relative configuration for 17 was determined as follows: first, the large coupling constant of H-3 (J 2-3 = 11.2, 4.2 Hz) indicated that the hydroxyl group (3-OH) was oriented equatorially (β-position) at C-3 [29,31]. Next, the ROESY correlations between H-18 (δ H 0.64) and H-20 (δ H 1.39); and H-17 (δ H 1.61) and H-21 (δ H 0.90) were determined as R configuration for the stereochemistry of C-20.…”
Section: Chemical Identification Of Compounds 1-19mentioning
confidence: 99%
“…Názorne to dokumentuje aj obrázok 6. Pri ebenovníkoch je však všeobecne známe, že plody sa môžu vytvárať partenokarpicky ako bezsemenné, t.j. bez opelenia (Chandler, 1965), čo sme určili aj pri hodnotení plodov pri všetkých druhoch. Pre konzumentov sú takéto plody veľmi vhodné.…”
Section: Výsledky a Diskusiaunclassified
“…The wood is esteemed as a rare and precious material [2], but nevertheless, there are very few reports on the chemical composition of the species. Santosh and Sandhya [3,4] isolated anthraquinones from the bark of the tree; Ganapaty et al [5] reported dimeric naphthoquinones from the roots; Lee et al [6] found that the leaf extract had excellent antioxidant activity; and Chen et al [7] isolated a lanostane-type triterpenoid. As for essential oils, Smith and Luz [8] analyzed the composition of that from the fruit.…”
mentioning
confidence: 99%